Biting deterrence and insecticidal activity of hydrazide-hydrazones and their corresponding 3-acetyl-2,5-disubstituted-2,3-dihydro-1,3,4-oxadiazoles against Aedes aegypti - KAYMAKÇIOĞLU, BEDİA (JOHN WILEY & SONS LTD, 2013)
Background Taking into account the improvement in insecticidal activity by the inclusion of fluorine in the hydrazone moiety, the authors synthesized new 4-fluorobenzoic acid hydrazides and 3-acetyl-2,5-disubstituted-2,3-dihydro-1,3,4-oxadiazoles, substituting a phenyl group or a heteroaryl ring carrying one or two atoms of F, Cl and Br, and investigated their biting deterrent and larvicidal activities against Aedes aegypti for the first time. Results The compound 3-acetyl-5-(4-fluorophenyl)-2-[4-(dimethylamino)phenyl]-2,3-dihydro-1,3,4-oxadiazole (17) produced the highest biting deterrent activity (BDI = 1.025) against Ae. Aegypti, followed by 4-fluorobenzoic acid [(phenyl)methylene] hydrazide (1). These activity results were similar to those of N,N-diethyl-meta-toluamide (DEET), which showed a proportion not biting of 0.80.92. When compounds 1 and 17 were tested on cloth worn on human volunteers, compound 1 was not repellent for some volunteers until present in excess of 500 nmol cm2, while compound 17 was not repellent at the highest concentration tested (1685 nmol cm2). In the larvicidal screening bioassays, only compounds 10, 11, 12 and 17 showed 100% mortality at the highest screening dose of 100 ppm against Ae. aegypti larvae. Compounds 11 and 12 with LD50 values of 24.1 and 30.9 ppm showed significantly higher mortality than 10 (80.3 ppm) and 17 (58.7 ppm) at 24-h post-treatment. Conclusion The insecticidal and biting deterrent activities were correlated with the presence of a halogen atom on the phenyl or heteroaryl substituent of the hydrazone moiety.
Keywords: hydrazide-hydrazones; 1,3,4-oxadiazoles; biting deterrent; repellent; larvicidal; Aedes aegypti; DIPTERA